A kinematic analysis of the breaststroke kick - Matheson, E.; Hwang, Y.; Romack, J.; Whiting, W.; Vrongistinos, K. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The study investigated the contribution of the ankle joint in the breaststroke kick using three dimensional kinematic analyses. Methodology included applying reference markers to the right leg using anatomical reference points and then videotaping twelve competitive swimmers performing the breaststroke. A Matlab script was used to calculate relative angles (between the foot and shank), angular and relative angular velocities, and linear velocities. The results of a linear regression at p<.05 showed that there was no statistical significance between the foot angular displacement and linear hip velocity, but there was a statistical significance between the local angular velocity and linear hip velocity in the anterior-posterior dimension. The results of the study suggest that the ankle joint and the foot are important contributors to the breaststroke kick.